Analysis of the financial condition and its importance for improving the efficiency of enterprise management - Nizomiddinov Jahonmirzo Zukhriddin oglu (Genius Journals, 2022)
Analysis of the financial condition of the company is an extremely important and urgent problem, both for each small business and for the state as a whole. Even in the recent past, when analyzing the work of the company, the main attention was paid to the rationing of working capital, various limits and funds were introduced, and profit was singled out from the main indicators. It was by this indicator that the financial condition of the company was judged. At present, such an approach is impossible: in the conditions of market relations, each company is interested in stability, solvency, economic growth opportunities, in modern methods of evaluation and analysis. In this regard, it is important not so much to take into account the amount of profit, return on equity, sales or assets, but to determine the entire amount of income received, the level of solvency and economic growth rates.
Keywords: Financial Condition; Analysis; Management Efficiency Improvement; Solvency